Bridging the Trust Gap in Wellness Innovation: A Strategic Roadmap for Consumer Adoption - Plotkin, Sean (Digital Repository of Theses, 2025)
We are witnessing a shift in how people approach health, moving beyond institutional care toward decentralized, self-directed wellness. With tools like red light beds, wearables, ice baths, and other biohacking technologies now available for at-home use, consumers are taking control of their health journeys. Yet, in this landscape of innovation and accessibility, a critical challenge emerges: how do people decide what to trust when regulation is absent? This dissertation investigates the behavioral and psychological dynamics of adopting preventive wellness technologies in unregulated markets. Drawing on a survey of 600 respondents and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) and Fuzzy-set Qualitative Comparative Analysis (fsQCA), the study develops and tests an extended conceptual model incorporating Technology Credibility (TC), Perceived Risk (PR), Health Motivation (HM), and Personal Innovativeness (PI). The findings confirm that Behavioral Intention (BI) is the most consistent predictor of Actual Use (AUT), with TC acting as a key enabler by linking beliefs to action. Additionally, facilitating conditions, social influence, and perceived risk significantly shape users’ intention and behavior. The fsQCA results revealed multiple pathways to adoption, supporting the principle of equifinality, that different combinations of motivations and contextual conditions can all lead to technology use. To better explain trust formation and consumer action, this study proposes the Wellness Trust Lifecycle Plus (W-TLC+) framework, a six-stage model that outlines how trust builds, shifts, and sustains over time in low-trust wellness ecosystems. W-TLC+ helps entrepreneurs and researchers understand not just why people adopt emerging wellness technologies, but also how to ethically build trust in their use and scale responsible innovation in unregulated spaces. This work contributes to theory by extending TAM and UTAUT into non-traditional contexts, and to practice by offering a strategic roadmap for fostering credibility, motivation, and adoption in decentralized health environments.